2018
DOI: 10.1016/j.jcot.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental knee replacement – Current perspectives

Abstract: Unicompartmental knee replacement (UKR) is an effective treatment for end-stage, symptomatic unicompartmental osteoarthritis of the knee. However, certain aspects of the procedure are still debated. These areas of discussion include patient selection criteria, implant design and the discrepancy in survival rates between national registries and independent case series. These may contribute in limiting the more widespread acceptance of unicompartmental knee replacement. The aim of this paper is to review the up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 62 publications
1
20
0
6
Order By: Relevance
“…This was thought to be around 6-12% of patients undergoing knee replacement surgery. 126 However, more recently, Campi et al, 126 reported that surgeons have widened the indications, especially for weight, age and activity, and up to 50% of patients may now be eligible for UKA.…”
Section: Overview Of the Trial Findings And Key Messagesmentioning
confidence: 99%
“…This was thought to be around 6-12% of patients undergoing knee replacement surgery. 126 However, more recently, Campi et al, 126 reported that surgeons have widened the indications, especially for weight, age and activity, and up to 50% of patients may now be eligible for UKA.…”
Section: Overview Of the Trial Findings And Key Messagesmentioning
confidence: 99%
“…9 Contraindicaciones para la artroplastia unicompartimental son: infección activa, enfermedad articular inflamatoria, ausencia de ligamento cruzado anterior, inestabilidad ligamentaria o contractura del ligamento colateral medial, e historia de osteotomía tibial previa. 10,11 Cirugía Robótica vs Cirugía Convencional En la actualidad, existe evidencia cada vez más sólida indicando que la cirugía robótica es una herramienta que mejora, en tiempo real, la precisión en el posicionamiento y elección de tamaño del implante.…”
Section: Indicaciones Y Contraindicaciones Para El Uso De La Técnica unclassified
“…Unicompartmental knee arthroplasty (UKA) is a valid treatment for end-stage knee osteoarthritis (OA), affecting a single femoro-tibial compartment [1]. The popularity of unicompartmental knee replacement (UKR) has increased as excellent functional outcomes and survival have been reported in long-term follow-up studies.…”
Section: Introductionmentioning
confidence: 99%